Evaluasi User Experience Aplikasi Mobile Belanja Online dengan Metode Design Thinking (Studi Kasus Lazada) - Arief Purba Sakti; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Lazada is one of the many online shopping platforms in Indonesia. However, Lazada still lags behind 2 other e-commerce giants, namely Shopee and Tokopedia. According to IDNTimes in a survey regarding the competition in the e-commerce industry during the end of 2021 and DailySocial.id regarding what e-commerce applications are often used, Lazada is still ranked 3rd compared to the other 2 competitors. This study aims to evaluate the user experience of the Lazada online shopping mobile application which focuses on the home page from the customer's perspective using usability testing methods and usability scale systems. The design thinking method is used in this study to find solutions to problems and improve the quality of the Lazada application user experience. In this study, a total of 12 problems were found which then resulted in 11 recommendations for improvement which were designed to become a prototype of an improvement design. The results of testing the old design and design improvements to 6 respondents in this study resulted in an increase in the three components tested, namely, the effectiveness component from an average of 83.33% to 100%, the efficiency component from an average of 0.039 goals/sec to 0.127 goals/ sec and the satisfaction component with the results in the old design, which is 45 which is included in the category of grade scale E and the adjective rating Awful becomes 77.5 which is included in the category of grade scale B and adjective rating Good.